Factors Influencing Public Interest in Choosing Sharia Insurance at PT. Asuransi Askrida Syariah Medan - Angelia Azira; Isra Hayati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
The research was conducted at PT Asuransi Askrida Syariah Medan with the aim of finding out what factors influence public interest in choosing Sharia Insurance at PT Asuransi Askrida Syariah Medan. This study used quantitative methods; Data collection was carried out using primary data derived from the distribution of questionnaires. The results revealed that the product has a significant positive influence on the selection of Sharia Insurance interests. Price does not have a significant positive effect on the selection of Sharia Insurance Interests. While Promotion has a significant positive influence on the Selection of Sharia Insurance Interests. Products, prices, and promotions significantly affect the Selection of Sharia Insurance Interests.